Pengembangan LKPD Berbasis Model Pembelajaran Index Card Match Materi Teks Deskripsi Kelas VII - Agung Satrio Putro (Universitas Palangka Raya, 2023)
This study aims to (1) develop student worksheets (LKPD) so as to produce LKPD products based on the index card match learning model for class VII descriptive text material, (2) describe the feasibility of LKPD based on index card match learning model material for class VII description text. This study uses the Research and Development (R&D) method using the 4-D model. In the 4-D model research there are 4 stages of research carried out namely Define, Design, and Development and Dissemination. The results of this study were that a student worksheet (LKPD) based on the index card match learning model was produced for class VII description text material with an average feasibility score of 89.23% from material experts and included in the very feasible category, 89.33% of design experts and included in the very decent category, 94% of Indonesian language study teachers and included in the very decent category. So it can be concluded that the Student Worksheet (LKPD) product based on the index card match learning model for class VII descriptive text material is suitable for use as additional teaching material in schools, especially class VII..